Ethical dilemmas of healthcare professionals and Covid-19 - Merzagora, Isabella; Caruso, Palmina; Travaini, Guido (Medicina e Morale, 2021)
The authors conducted research on the subject of ethical choices in the pandemic period (April 2020) on a sample of 1,009 people by administering a special online questionnaire (web interviews). At the time of survey 10% of this sample used to work in the health area. Starting from the analysis of these data and in the light of the reference literature and the recommendations of SIAARTI / SIMLA "Decisions for intensive care in case of disproportion between care needs and available resources during a COVID-19 pandemic", the authors propose some thoughts on the subject of ethical dilemmas.